2017
DOI: 10.1111/ajsp.12164
|View full text |Cite
|
Sign up to set email alerts
|

Does religious priming increase the prosocial behaviour of a Japanese sample in an anonymous economic game?

Abstract: We examined the effect of religious priming on a Japanese sample in an anonymous dictator game whereas previous studies on religious priming on prosociality had mainly been conducted within Western contexts. The current study attempted to examine whether religion increases prosocial behaviour in a Japanese sample through the replication of 'God is Watching You' (Shariff & Norenzayan, 2007) where it was found that participants primed with religionrelated words and secular justice-related words behaved more pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…Penelitian yang dilakukan oleh (Miyatake & Higuchi, 2017) menunjukkan bahwa orientasi keagamaan dapat meningkatkan perilaku prososial individu dimana perilaku tersebut merupakan dasar dalam menumbuhkan perilaku membantu, berbagi antar sesama. Konsep yang ditanamkan adalah bahwa dalam kegiatan mereka sehari hari selalu diawasi oleh tuhan.…”
Section: Simpulan Dan Implikasiunclassified
“…Penelitian yang dilakukan oleh (Miyatake & Higuchi, 2017) menunjukkan bahwa orientasi keagamaan dapat meningkatkan perilaku prososial individu dimana perilaku tersebut merupakan dasar dalam menumbuhkan perilaku membantu, berbagi antar sesama. Konsep yang ditanamkan adalah bahwa dalam kegiatan mereka sehari hari selalu diawasi oleh tuhan.…”
Section: Simpulan Dan Implikasiunclassified
“…Finally, on January 18, 2018, we sent out a call for religious priming experiments on the SPSP listserv. Our efforts revealed one new experiment that used implicit religious priming in a Japanese sample [41].…”
Section: Studymentioning
confidence: 99%
“…Effect sizes were Hedges' g. For studies that appeared in Gomes & McCullough[25], we determined Hedges' g and the associated variance from theirTable 3. For Miyatake & Higuchi[41], we calculated Hedges' g and the associated variance from the reported t value and sample sizes. We then added the results of our own Experiment 1 and Experiment 2 for implicitly primed subjects only.…”
mentioning
confidence: 99%
“…Importantly, to date, there is only one published study that has investigated religious priming effects using a Japanese sample [50]. Miyatake and Higuchi [50] attempted a direct replication of Shariff and Norenzayan [6], utilizing identical methodology, and found that visual religious priming did not affect individuals' pro-sociality.…”
Section: Introductionmentioning
confidence: 99%